Adoption of Islamic banking products and services among UniSZA students - Mawaddah Suwaimi
Islamic banking has been a crucial part in the banking industry of Malaysia for over thirty years and has successfully contributing to the economic growth of the country. Since its emergence in year 1983, Islamic banking industry has shown a slow progress compared to its counterpart every year. The market share only achieved an average of 34.3 percent in Islamic assets, deposits and financing since it was launched and it is still dominated by the conventional banking. Meanwhile, Malaysia government hopes to push it over 40 percent by 2020. Therefore, this study took place to examine some important factors that affected the adoption of Islamic banking products and services especially on Islamic deposit and financing schemes offered. This study only focuses on young generation which consists of students in higher educational institution. The data is based on samples gathered from students of Universiti Sultan Zainal Abidin (UniSZA). 310 out of 373 distributed questionnaires were returned and usable to analyse. IDM SPSS Version 23.0 was used to analyse the data and to test the hypotheses. Descriptive analysis, Independent Samples t-test, ANOVA, Correlation analysis and Multiple Regression analysis were the statistical tools employed to address the objectives of the study. The findings show that awareness ofIslamic banking attributes, uncertainty and perceived information quality are the factors that affected the adoption of Islamic banking products and services among UniSZA students. However, promotional efforts is not significant to the adoption of Islamic banking products and services.